Exploring The Impact Of Narrative Techniques On Audience Satisfaction In Contemporary Chinese Commercial Films In The New Period Of China (International Journal of Environmental Sciences, 2025)
Today, audience satisfaction is a major factor in a film's success in China's New Period commercial films. Using the narrative technique of storytelling methods is the cornerstone of making any film. However, there is insufficient academic evidence indicating the effect of narrative techniques on audience satisfaction in contemporary Chinese commercial films in the new period of China. Hence，the objective of this study is to investigate the influence of narrative techniques on audience satisfaction in commercial films from the New Period of China. On top of that, the study also attempts to comprehend the mediating influence of perceived technique usefulness on the overall satisfaction of the films and the responses of the audience. This quantitative study collected data from 390 individuals aged 18–50+ in Shanghai, Beijing, and Guangzhou, using questionnaire items adapted from previous research on seamlessness, presence, interoperability, concurrence, perceived technique usefulness, and audience satisfaction. The data were analyzed using reliability test, confirmatory factor analysis, correlation analysis and hypothesis testing. The findings reveal that seamlessness, presence, and interoperability of narrative techniques significantly enhance audience satisfaction, particularly when perceived as useful. Therefore, Perceived techniques' usefulness can perceive acts as a mediating factor. However, excessive concurrence of techniques can negatively impact satisfaction by overwhelming the audience. The theoretical significance of the study accentuates the knowledge add-up in the corresponding sector of film industry of thinking audience satisfaction in the relationship with narrative technique usage. The findings also propose that only by respecting the act of cinematographic narrative can the industry create works of art that are more artistically creative and more in line with the aesthetic needs of film audiences and the other stakeholders in this industry.